THE DEVELOPMENT OF AN ACTIVE LEARNING MANAGEMENT MODEL BASED ON A HIGH-LEVEL SYSTEMIC APPROACH TO ENHANCE LEARNING AND INNOVATION SKILLS OF LOWER SECONDARY SCHOOL STUDENTS - Treekaew, Apisit; Namponwatthanakul, Thanatep; Assawasowan, Jutiporn (Journal of MCU Nakhondhat, 2025)
This research article aimed to: 1) Examine the components of an Active Learning Management Model based on Advanced Systems Thinking to Enhance Learning and Innovation Skills for Lower Secondary School Students, 2) Develop the Active Learning Management Model, and 3) Evaluate the effectiveness of the developed Learning Management Model. The study employed a Research and Development (R&D) process. The sample comprised 31 Grade 9 students from Sichonkunathanwittaya School, Nakhon Si Thammarat Province, selected through purposive sampling at the classroom level (one classroom). The research instruments included the learning management model and lesson plans developed according to the model. Data collection tools were an Academic Achievement Test, a Learning and Innovation Skills Assessment and a Satisfaction Evaluation Questionnaire. The data were analyzed using mean ( ), standard deviation (S.D.), t-test, and efficiency analysis. The research findings revealed: 1) The Learning Management Model consisted of four components: 1.1) Principles/Concepts, 1.2) Objectives, 1.3) Learning Steps/Process, and 1.4) Measurement and Evaluation. 2) The development of the Learning Management Model resulted in the 5I Model, which comprises five steps: Step 1: Ignite Thinking and Accumulate Knowledge, Step 2: Analyze and Systemize Knowledge, Step 3: Practice and Conclude, Step 4: Communicate Knowledge and Present, and Step 5: Integrate Knowledge and Evaluate for Value Creation. And The model was found to have an efficiency that met the criterion of 80/80. and 3) The evaluation of the model's effectiveness showed that the post-test academic achievement was significantly higher than the pre-test at the .05 statistical level. The overall learning and innovation skills were at the Very Good level, and the students' overall satisfaction with the model was at the Highest level.